If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3w + -2 = -14 Reorder the terms: -2 + -3w = -14 Solving -2 + -3w = -14 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -3w = -14 + 2 Combine like terms: -2 + 2 = 0 0 + -3w = -14 + 2 -3w = -14 + 2 Combine like terms: -14 + 2 = -12 -3w = -12 Divide each side by '-3'. w = 4 Simplifying w = 4
| 2v=-2v+36 | | 7d(4x-2)= | | 6m^2+8m=0 | | -5u=u-16 | | Z/10-6=5 | | 7-2/3z | | y-9=-7(x+3) | | -3+2=4(1-1) | | 3(p+6)-5p=10-4p | | -119=2n-5(7n+4) | | 5y-4x-7=10fory | | 2.5c=18 | | 14.05+.11(x+3)=14.55-.13x | | 8.3=2x/(0.2-x) | | 9+y=-23 | | 6y-3z-8y+4z= | | 5n+5=200 | | 3=3(1)+2 | | A+(-19)=3 | | 7-2+x=12 | | 0/7-6/4 | | 213-y=291 | | 2x+2y=57 | | X(X+3)=192 | | 3*(2/3) | | 295=-x+114 | | 5y-4x-7=10 | | 15-2(y-3)=6(2y+6)-5y | | 2-9(1-8a)=32 | | -9(10+6x)=3x-33 | | 6x-3=651 | | 0+1=2(5-3) |